Evaluation of Response Processes to the Danish Version of the Dutch Multifactor Fatigue Scale in Stroke Using the Three-Step Test-Interview - Dornonville de la Cour, Frederik L.; Norup, Anne; Schow, Trine; Andersen, Tonny Elmose (Frontiers in Human Neuroscience, 2021)
Validated self-report measures of post-stroke fatigue are lacking. The Dutch Multifactor Fatigue Scale (DMFS) was translated into Danish, and response process evidence of validity was evaluated. DMFS consists of 38 Likert-rated items distributed on five subscales: Impact of fatigue (11 items), Signs and direct consequences of fatigue (9), Mental fatigue (7), Physical fatigue (6), and Coping with fatigue (5). Response processes to DMFS were investigated using a Three-Step-Test-Interview protocol, and data was analysed using Framework Analysis. Response processes were indexed on the following categories: i) “congruent”, response processes were related to the subscale construct, ii) “incongruent”, response processes were not related to the subscale construct, iii) “ambiguous”, response processes were both congruent and incongruent or insufficient to evaluate congruency, and iv) “confused”, participants did not understand the item. Nine adults were recruited consecutively 10 to 34 months post-stroke (median = 26.5) at an outpatient brain injury rehabilitation centre in 2019 (five females, mean age = 55 years [SD=6.3]). Problematic items were defined as <50% of response processes being congruent with the intended construct. Of the 38 items, five problematic items were identified, including four items of Physical fatigue and one of Mental fatigue. In addition, seven items posed various response difficulties to some participants due to syntactic complexity, vague terms, a presupposition, and a double-barrelled statement. In conclusion, findings elucidate the interpretative processes involved in responding to DMFS post-stroke, strengthening the evidence base of validity, and guide revisions to mitigate potential problems in item performance.